2021
DOI: 10.1007/s40820-021-00708-1
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring the Potassium-Ion Storage Enhancement in Iron Selenide with Ether-Based Electrolyte

Abstract: As one of the promising anode materials, iron selenide has received much attention for potassium-ion batteries (KIBs). Nevertheless, volume expansion and sluggish kinetics of iron selenide result in the poor reversibility and stability during potassiation–depotassiation process. In this work, we develop iron selenide composite matching ether-based electrolyte for KIBs, which presents a reversible specific capacity of 356 mAh g−1 at 200 mA g−1 after 75 cycles. According to the measurement of mechanical properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…This result indicates less damage to the electrode during the cycles, speculating that the DME-KFSI electrolyte contributes to the protection of the electrode. [45][46][47] To further confirm the differences between the SEI layers, the corresponding forcedisplacement curves and their detailed analyses were obtained by AFM, as shown in Fig. 3c-f.…”
Section: Resultsmentioning
confidence: 99%
“…This result indicates less damage to the electrode during the cycles, speculating that the DME-KFSI electrolyte contributes to the protection of the electrode. [45][46][47] To further confirm the differences between the SEI layers, the corresponding forcedisplacement curves and their detailed analyses were obtained by AFM, as shown in Fig. 3c-f.…”
Section: Resultsmentioning
confidence: 99%
“…EIS spectra of FeSe 2 @RGO electrode with DME-based and EP-based electrolytes (j) before and (k) after 50 cycles. Reproduced from Ref., [78] under the terms of the CC BY 4.0 license. most of literature, amorphous chalcogens conversion reaction is lack of detailed analysis.…”
Section: Discussionmentioning
confidence: 99%
“…discharge process, which could prevent the final conversion product of K 2 Se dissolved into electrolytes to reach better performance (Figure 11c) Next, Li et al reported FeSe 2 @rGO as anode material of PIBs, and used 1 M, 5 M KFSI in DME and 1 M KFSI in EC/PC (1 : 1, v/v) marked as EP electrolyte system for testing, respectively. [78] Among them, the 1 M KFSI in DME system observed that the voltage did not reach 3 V during the first charge. It is presumed that the low concentration electrolyte could not inhibit the dissolution of polyselenides.…”
Section: Interaction With Electrolytes and Metal Chalcogenidesmentioning
confidence: 99%
See 2 more Smart Citations